Analisis Tingkat Penerimaan Pengguna Terhadap Aplikasi Beli.In Menggunakan Technology Acceptance - Tansie, Leonardo Patrick; Rahman, Syaiful; Arianti, Arianti (JTRISTE, 2024)
This study aims to analyze the level of user acceptance towards the Beli.in application using the Technology Acceptance Model (TAM). TAM was chosen as the analytical tool to understand the factors influencing user acceptance of the technology. The study focused on three TAM variables: perceived ease of use, perceived usefulness, and actual use. Data were collected from 32 respondents using a questionnaire. The research findings showed that respondents positively accepted the Beli.in application. The percentage of agreement for the perceived ease of use variable reached 74.06%, indicating that the application is considered easy to use in the process of searching and obtaining information about products. The perceived usefulness variable reached a percentage of 67.5%, indicating that the application is considered beneficial in helping users find daily necessities. However, the actual use variable had a lower percentage at 52.5%, indicating that there is still room to improve application usage. In conclusion, the results of this study provide an overview of user perceptions towards the Beli.in application.